The Constraints and Problems in Team Performance Management - Urlych, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
A wide range of factors can affect team performance: setting clear and achievable goals, allocating individual work, utilizing an individual’s skills, monitoring performance, maintaining team cohesion and identity, being able to handle internal conflicts, maintaining relationships with other teams, systems and resources available to teams and the quality of leadership. These problems and constraints affecting team performance management (TPM) are found on a global scale irrespective of a country’s individual work culture. This paper presents the nature of team performance management in order to discuss common TPM problems and constraints in the context of worldwide research findings. Environmental factors and team dynamics consistently influence team effectiveness. It is now clear that there is a need for future research to look at the complexity of team dynamics over time.